2019
DOI: 10.1177/0018726718815555
|View full text |Cite
|
Sign up to set email alerts
|

Practices and knowing in transnational knowledge-intensive service provision

Abstract: How do professionals at different locations within a firm collaborate to provide services across borders? This article addresses how knowledge-intensive service provisions are coordinated across borders, time zones and expertise. Empirical material from two engineering firms providing services to a global customer base are analysed, comprising over 100 interviews and over 20 days of observation. Concepts from practice theory are used, locating questions of knowledge in the realm of practical action. Findings d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…This is, I believe, because actors are new to the phenomenon. However, challenging the suggestion that the knowing produced by collective learning fosters participation (e.g., Hydle and Hopwood 2019;Pyrko, Dörfler, and Eden 2017), I found that knowing is Janus faced and can have negative implications for participation under specific circumstances. First, actors are novel to the field and lack an in-depth understanding of its dynamics.…”
Section: Discussioncontrasting
confidence: 59%
“…This is, I believe, because actors are new to the phenomenon. However, challenging the suggestion that the knowing produced by collective learning fosters participation (e.g., Hydle and Hopwood 2019;Pyrko, Dörfler, and Eden 2017), I found that knowing is Janus faced and can have negative implications for participation under specific circumstances. First, actors are novel to the field and lack an in-depth understanding of its dynamics.…”
Section: Discussioncontrasting
confidence: 59%
“…It is even more curious given several studies have the 'global' dimension built into their analysis (e.g., Greenwood and Suddaby, 2006) and many are specifically concerned with theorizing the (organizational, leadership, HRM, etc.) implications of PSFs transforming themselves into 'global' firms (e.g., Aharoni, 1996;Boussebaa, 2009;Breunig et al, 2014;Brock and Hydle, 2018;Fenton and Pettigrew, 2000, 2003, 2006Greenwood et al, 2010;Hydle and Hopwood, 2019;Jones, 2005;Løwendahl, 2000;Rose and Hinings, 1999;Segal-Horn and Dean, 2009;Silver et al, 2009). A close reading of these reveals scholars to be theorizing the 'global' almost exclusively based on research conducted in the West.…”
Section: Producing a False Universalismmentioning
confidence: 99%
“…For example, the literature shows that the organisational structure of the workplace as manifested in rules, instructions and guidelines, the culture expressed through motives and values, and material resources such as premises, tools and equipment constitute important parts of a work practice (c.f. Hydle andHopwood 2019, Schürmann andBeausaert 2016;Boud et al 2009;Billett 2004). Another prerequisite for informal learning is that there are opportunities to reflect on one's work in the day-to-day practice (Boud 2006).…”
Section: Informal Workplace Learningmentioning
confidence: 99%
“…Learning constitutes an important part of working and can take place through actions and interactions with colleagues (Boud et al 2009), for example, when problems and challenges are encountered that need to be addressed in order to be able to move forward (Boud and Hager 2012). Thus, learning at work does not primarily take place in the course of formal activities, but emerges through working with peers in informal ways (Hydle and Hopwood 2019). The literature also shows that informal learning activities are often initiated by triggers (Marsick and Watkins 1997).…”
Section: Informal Workplace Learningmentioning
confidence: 99%